The Effect of Acupuncture on Post-Cancer Fatigue and Well-Being for Women Recovering from Breast Cancer: A Pilot Randomised Controlled Trial. Issue 1 (March 2013) - Smith, Caroline; Carmady, Bridget; Thornton, Charlene; Perz, Janette; Ussher, Jane M
Objective: To determine the feasibility and acceptability of acupuncture in managing fatigue and well-being in breast cancer survivors. Methods: A randomised controlled trial compared acupuncture was with sham acupuncture and wait list controls was performed in Sydney, Australia. A total of 30 women with fatigue following breast cancer treatment participated in the trial. Women received six sessions of acupuncture over 8 weeks. Outcomes related to an assessment of interest to participate in the trial and identification of appropriate recruitment strategies, appropriateness of eligibility criteria and compliance with treatment attendance. Clinical outcomes assessed fatigue and well-being. In-depth interviews were undertaken with seven women, who described their experience of acupuncture. Results: Our study demonstrated feasibility with appropriate trial entry criteria, good acceptability and treatment compliance with the study interventions, and with the completion of outcome forms. There was a significant reduction in fatigue for women receiving acupuncture compared with control after 2 weeks mean difference (MD) 5.3, 95% CI 4.5 to 6.2, p=0.05, and a significant improvement in well-being at 6 weeks for acupuncture compared with the sham and wait list control, MD 2.7, 95% CI 2.1 to 3.2, p=0.006. Women described their experience of acupuncture positively, and interview data may also offer explanations for the improved outcomes of well-being, with women reporting an improvement in sleep, mood and relaxation. Conclusions: Fatigue is a common symptom experienced by people recovering from treatment, and an appropriately powered trial to evaluate the effect of acupuncture is needed. Clinical Trial Registration: Australian New Zealand Clinical Trials Registry, www.anzctr.org.au ACTRN12610000720011.